Spigelian hernia diagnosed in a newborn: A case report - Nicole Chicoine; Frederick Rescorla (Journal of Pediatric Surgery Case Reports)
Introduction: Spigelian hernias represent only 0.1–0.2 % of all abdominal wall hernias and are infrequently encountered in pediatric patients. Limited literature surrounding pediatric Spigelian hernias exists, and there is no uniform or optimal surgical repair technique. Case presentation: A term female with unremarkable prenatal history presented a left-sided Spigelian hernia at birth that contained loops of bowel, by physical examination and ultrasound. The hernia was easily reducible, so she was discharged with a plan for an elective repair at a later point. At 8 months of age, she underwent an abdominal wall ultrasound that showed a defect of 6 cm in length. She underwent elective repair at 9 months of age due to parental preference in the setting of an enlarging defect size. The hernia repair was done through a combination of laparoscopic and open techniques. The laparoscopy part, which consisted in one port placed in the umbilicus for a camera, enabled visualization of the suspected hernia site, confirm the proper approximation of the lateral and medial borders of the hernia, and helped avoid any intra-abdominal injuries during the repair. The repair itself was completed in an open manner with interrupted sutures in a top to bottom approach, in a transverse orientation. The patient recovered well from the operation. At 1 year of follow up she has shown no signs of recurrence. Conclusion: Congenital pediatric Spigelian hernias can be successfully repaired using a combination of laparoscopy and open approach. The addition of a laparoscopy allows proper visualization of the intra-abdominal side of the repair.